Design of a New TPACK-SAMR Pedagogical Training Model Based on MOODLE to Develop 21st-Century Learning Design Skills - Nurwidayati, Pityarini; Satyawati, Sophia Tri; Mawardi (Jurnal Paedagogy, 2026)
This study aims to develop and validate a new MOODLE-based TPACK-SAMR pedagogical training model to enhance teachers’ competence in designing learning scenarios that foster 21st-century skills. This research and development study adopted the Borg and Gall model and was conducted at Satya Wacana Christian High School using a mixed-methods approach. The participants consisted of 12 teachers and one principal. Qualitative data were collected through interviews, document analysis, observations, questionnaires, and focus group discussions (FGDs), while quantitative data were obtained through questionnaires and pretest-posttest assessments. Qualitative data were analyzed using thematic analysis involving data reduction, data display, and conclusion verification. Quantitative data were analyzed using descriptive statistics, including scoring, percentages, and categorization, while the effectiveness of the training model was evaluated using inferential statistical analysis. The study resulted in a validated MOODLE-based TPACK-SAMR pedagogical training model designed to strengthen teachers’ capacity to develop 21st-century learning scenarios. The model achieved an average validation score of 95.02% (Excellent) from two instructional design experts and 84.98% (Good) from one e-learning expert. In addition, participants’ evaluation of the training model reached 95.21% (Excellent). The post-test results showed a statistically significant improvement in teachers’ competencies (Sig. = 0.000, p < 0.05), indicating that the proposed MOODLE-based TPACK-SAMR pedagogical training model effectively enhances teachers’ ability to design 21st-century learning scenarios. This model contributes to teachers’ professional transformation from technology users to digital learning designers capable of developing students’ Higher-Order Thinking Skills (HOTS) and 21st-century 4C competencies. Consequently, it provides an innovative pedagogical framework for strengthening teachers’ digital pedagogical competence and addressing the evolving demands of education in the era of digital transformation.